Choosing the most appropriate PROM for clinical studies in sports medicine. (12th January 2021) - Comins, Jonathan D.; Brodersen, John; Siersma, Volkert; Jensen, Jonas; Hansen, Christian Fugl; Krogsgaard, Michael R.
Abstract : Choosing the most appropriate patient‐reported outcome measure (PROM) for a clinical study is essential in order to achieve trustworthy results. This choice will depend on (a) the objective of the study and hence the research question; (b) the choice of a theoretical framework, such as the World Health Organization's International Classification of Functioning, Disability, and Health (ICF); (c) whether there currently is a PROM that possesses high content validity and high construct validity for the specific patient group and objective, and if not; (d) the decision on whether to use a suboptimal PROM or develop and validate a new PROM. This paper presents the steps that should be followed in order to assess the relevance of PROMs and suggests ways to enhance the choice depending on the goal of the study.